Contribution of Mountaineering Tourism to Nepalese Economy - Vaidya, Rashesh (Nepalese Journal of Hospitality and Tourism Management, 2023)
Snow-capped mountains and Nepal are analogous. The mountains have become synonymous with Nepal. The mountains that run along Nepal's northern border have become not only a symbol of the country but also an important part of its economy. The nation and the Nepalese tourism industries have been branding the snow-capped mountains to attract tourists from around the world. Mountaineers around the world visit Nepal to conquer the mountains. In the process of mountaineering, Nepal has been generating a good amount of revenue. Hence, the paper tries to find out the contribution of mountain tourism to the Nepalese economy. For this purpose, the paper followed a correlation research design. The paper found a perfect connection between the number of mountaineers arriving in Nepal and the royalty collection from them. Hence, the increasing number of mountaineers ultimately determined the royalty collection from mountaineering. Nevertheless, the paper also disclosed that the number of expedition teams and mountaineers arriving in Nepal for mountaineering has a positive connection with the real gross domestic product (GDP) of Nepal.